Experimental and Numerical Study of the Uniaxial Compressive Stress-Strain Relationship of a Rock Mass with Two Parallel Joints - Xiong L. X.; Yuan H. Y.; Zhang Y.; Zhang K. F.; Li J. B. (Archives of Civil Engineering, 2019)
A “rock bridge”, defined as the closest distance between two joints in a rock mass, is an important feature affecting the jointed rock mass strength. Artificial jointed rock specimens with two parallel joint fractures were tested under uniaxial compression and numerical simulations were carried out to study the effects of the inclination of the rock bridge, the dip angle of the joint, rock bridge length, and the length of joints on the strength of the jointed rock mass. Research results show: (1) When the length of the joint fracture, the length of the rock bridge, and the inclination of the rock bridge stay unchanged, the uniaxial compressive strength of the specimen gradually increases as the inclination of the joint fracture increases from 0°to 90°. (2) When the length of the joint fracture, the length of the rock bridge, and the inclination of the joint fracture stay unchanged, the uniaxial compressive strength of the specimen shows variations in trends with the inclination of the rock bridge increasing from 30° to 150° (3). In the case when the joint is angled from the vertical loading direction, when the dip angle of the joint fracture, the inclination of the rock bridge, and the length of the rock bridge stay unchanged, the uniaxial compressive strength of the specimen gradually decreases with an increasing length of joint fracture. When the dip angle of the joint fracture, the inclination of the rock bridge, and the length of the joint fracture stay unchanged, the uniaxial compressive strength of the specimen does not show a clear trend with an increase of the length of the rock bridge.